What Is the Optimal Treatment of Atrophic Scaphoid Non-Union? - Çirakli, A.; Öner, K.; Pişkin, A.; Yildiz, M.; Uzun, E.; Göçer, H. (Derman Medical Publishing, 2016)
Aim: To evaluate the efficacy of the treatment method of autogenous iliac wing or radius bone graft and fixation with screw applied to cases of scaphoid non-union. Material and Method: A retrospective evaluation was made of 89 cases between 2000 and 2014. Postoperative measurements were taken of both wrists’ movement with a goniometer and muscle strength was assessed with a dynamometer. Fractures were evaluated radiologically according to the Herbert-Fisher System and the functional results according to the Herbert-Fisher Classification System and the Mayo Clinic Modified Wrist Scoring System. The data were input to the SPSS system and evaluated with the Shapiro-Wilk test. Results: Non-union were on the right side in 47 and the left side in 42 cases. The fracture was seen to be in the waist in 60 cases (67.5%), in the proximal third in 27 cases (30.3%) and in the distal third in two cases (2.2%). The mean follow-up period was 16.4 months (range, 5-72 months). Definitive findings of union were observed in 71 cases. The mean time to union was 14.9 weeks (range, 8-40 weeks). Discussion: The grafting procedure applied is an invasive technique but if it is considered that there are negative effects of open surgery on the feeding of the scaphoid bone, then in the treatment of scaphoid non-union which is atrophic non-union, ultimately autogenous bone grafting and screw fixation is a safe and successful method and because of the pain created by an iliac wing graft, radius distal bone graft can be considered more appropriate. © 2016, Journal of Clinical and Analytical Medicine. All rights reserved.
Skafoid Kaynamamalarında Optimal Tedavi Nedir?
Keywords: Autografting; Non-Union; Scaphoid; Surgical Treatment